The risk of low energy availability in Chinese elite and recreational female aesthetic sports athletes - Meng, K.; Qiu, J.; Benardot, D.; Carr, A.; Yi, L.; Wang, J.; Liang, Y. (Journal of the International Society of Sports Nutrition, 2020)
Background: Low energy availability (LEA) is a medical condition observed in athletes, with a higher prevalence in aesthetic sports. For the first time, this study evaluated the relative prevalence of LEA in female elite athletes (ELA) and recreational athletes (REA) in aesthetic sports in China. Methods: Female athletes from 6 sports (trampolining, rhythmic gymnastics, aerobics, dance sport, cheerleading and dance) were recruited, including ELA (n = 52; age = 20 ± 3) on Chinese national teams and REA (n = 114; Age = 20 ± 2) from Beijing Sport University. Participants completed 2 online questionnaires to assess LEA and eating disorder risk. These included the Low Energy Availability in Females Questionnaire (LEAF-Q), which provided information on injury history, gastrointestinal function and menstrual history, and the Eating Disorder Inventory-3 Referral Form (EDI-3 RF). For a sub-group of elite athletes (n = 14), body composition, bone mineral density, and blood serum were also quantified. Results: A total of 41.6% of participants (n = 69) were at increased risk of LEA, and 57.2% of participants (n = 95) were classified as high in eating disorder risk. For ELA vs. REA, there was a significantly higher prevalence of LEA risk (55.8% vs. 35.1%; p = 0.012) and amenorrhea (53.8% vs. 13.3%; p < 0.001). Elite athletes at increased risk of LEA had significantly lower estradiol (p = 0.021) and whole-body BMD (p = 0.028). Pearson correlations indicated that the whole-body BMD (r = - 0.667, p = 0.009) correlated negatively with LEAF-Q score. Conclusions: Results of this study indicate that there is a risk of LEA in female Chinese athletes within aesthetic sports, and significantly higher prevalence of increased LEA risk observed in ELA than in REA. Chinese coaches and sports medicine staff working elite female athletes in aesthetic sports should develop strategies to reduce the prevalence of LEA.